Présence de L'Art Naïf en Europe. - Vallier, Dora (Laval : Siloë, 1997)
Rousseau, Henri ; Lefranc, Jules ; Bauchant, André ; Beleys, Colette ; Baglione, Antigore ; Moigne, Simone Le ; Salaun, André ; Petit, Pilar De Aristégui ; Saiz-Heres, Bélen Saro ; Barba, Mercédès ; Pasotti, Bernardo ; Pereoli, Enrico ; Güdel, Helen ; Carsau, Jan ; Raffler, Max ; Trillhaase, Adalbert ; Marx, Sophia ; Odenthal, Eduard ; Neervoort, Leo ; Zomer, Anna ; Nikifor ; Beller, Ilex ; Korovkin, Albert Nikolayvich ; Stepanov, Sergey Georgiyevich ; Bendoukidze, Nodaria ; Steberl, Ondrei ; Ignatov, Gueorgui ; Bahunek, Sava SavovBranko ; Filipovic, Franjo ; Generalic, Josip
biografie
Présence de L'Art Naïf en Europe, Biennale de Laval, 30 mai - 7 septembre 1997
Frans
boek
Keywords: Europa